Searching for Chinese Song Dynasty fans related to cultural dimensions - Zhan, Zhi; Chandhasa, Rosjana (Journal of Ecohumanism, 2024)
This study examines the formation of fan culture in China during the Song Dynasty, focusing on the cultural expressions inherent in fan making. With the aim of exploring the fan culture of the Song Dynasty, qualitative research methods and descriptive analysis were employed. The cultural dimensions under investigation include connotations, beliefs, lifestyles, aesthetics, materials, and craftsmanship. To conduct this investigation, the researcher visited the Guangdong Provincial Museum and the Guangdong Provincial Arts and Crafts Mall, where a variety of fans were studied and analyzed for their design and usage patterns. The Song Dynasty in China integrated fan-making with the prevailing culture of the era. Through both practical function and distinctive design, the art adorning the fan faces showcased a wealth of calligraphy and painting from Song Dynasty culture. Over generations, this amalgamation evolved into a unique art form. During the Song Dynasty, fan culture thrived, with fan painting transcending mere decoration to become a distinct genre of painting and calligraphy. Artists of the period often utilized the fan's shape as a canvas, showcasing a diverse array of subjects and an exquisite artistic style. Both in design and production, fan makers of the Song Dynasty achieved remarkable levels of artistry. Fans were crafted from a variety of materials and in different shapes, including Paper Fans, KeSiTuan Fans, and Round Silk Fans, each exhibiting round, square, or hexagonal forms, respectively. The paintings and calligraphy adorning these fans were exceptionally refined, frequently executed by renowned artists such as Su Shi, Mi Fu, and Wen Tong, whose works adorned fan surfaces commonly. These artworks not only demonstrated the artists' skill but also reflected the aesthetic and cultural ethos of Song Dynasty society.